Functional dairy products enriched with plant ingredients - Stanislav A. Sukhikh; Lidiia A. Astakhova; Yuliya V. Golubcova; Andrey A. Lukin; Elizaveta A. Prosekova; Irina S. Milent`eva; Natalia G. Kostina; Aleksandr N. Rasshchepkin (Foods and Raw Materials, 2019)
Milk and dairy products are staple foods in the diet of all social groups. Plant additives are of multifunctional use in the dairy industry. Wild plants are a source of vitamins, minerals, and other biologically active substances. Due to these compounds, they improve digestion, cardiovascular activity, and emotional state. This review describes the latest trends in creating functional milk drinks enriched with plant components. They include drinks based on whole milk and cream, dairy by-products (whey, buttermilk), as well as fermented milk drinks with probiotic cultures (kefir, drinking yogurt). We found that aqueous extracts were most commonly introduced into milk raw materials. Fruits and berries were dried and added to milk raw materials in the powder form. Special attention was paid to ‘hairy roots’ as a promising technology for producing various functional foods. In addition to being economically viable, this technology can help us expand the range of plant materials with endangered species. Functional milk-based drinks enriched with plant extracts can improve the immune system and be used as part of supportive therapy. They are also suitable for daily use to replenish the balance of essential nutrients. These properties make their production a promising direction in the dairy industry.